ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BIOLOGI BERKARAKTER KELAS XI SMA NEGERI UNTUK STANDARISASI RPP DI KABUPATEN DHARMASRAYA - Rumtika, Maya; Mulyati, Mulyati; Risdawati, Renny (STKIP PGRI Sumbar, 2013)
ABSTRACTOne task of the teacher is to create learning tools that RPP. RPP is a plan that describes the procedures and learning management to achieve one or more that KD has been described in the syllabus . At SMA Negeri 1 Pulau Punjung and 2 Pulau Punjung lesson plans are identical. This study aims to determine the standardized lesson plans created by teachers of biology in Class XI Semester II in accordance with the standards IPKG-1 which has been developed by Mulyati, etc (2013). This research is a descriptive study. The population in this study is the RPP biology teacher in Class XI SMA Dharmasraya. Sampling techniques in the study was stratified random sampling. Sources of data in this study is the RPP biology teacher in class XI SMA Dharmasraya . The data were processed using percentage techniques. Results of this study revealed that the CSP component analysis completeness subject teacher of biology at SMA in the District Dharmasraya with an average of 55 %. Results of the relationship between indicators of valuation analysis, learning objectives, learning materials, teaching methods, instructional media, learning activities and evaluation of the RPP subject teacher of biology at SMA in the district Dharmasraya with an average of 64 % considered pretty standard. The conclusion that the terms of the completeness of the components RPP Subject teacher of biology at Dharmasraya is 55 % and RPP SMA biology Class XI For Standards in Dharmasraya which 64 % were categorized enough standard.